2023
DOI: 10.4014/jmb.2310.10003
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Protaetia brevitarsis Larvae Ameliorates Chronic Ethanol-Induced Hepatotoxicity in Mice via AMPK and TLR-4/TGF-β1 Pathways

Hyo Lim Lee,
Jong Min Kim,
Min Ji Go
et al.

Abstract: This study evaluated the hepatoprotective effect of fermented Protaetia brevitarsis larvae (FPB) in ethanol-induced liver injury mice. As a result of amino acids in FPB, 18 types of amino acids including essential amino acids were identified. In the results of in vitro tests, FPB increased alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) activities. In addition, FPB treatment increased cell viability on ethanol- and H 2 O 2 -indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 79 publications
(121 reference statements)
1
5
0
Order By: Relevance
“…In this study, in the results of the analysis of the composition of fatty acids in FPB, palmitic acid, oleic acid, and linoleic acid were the major fatty acids detected ( Table 1 ). Consistent with our study, previous studies have reported that the essential amino acid and unsaturated fatty acid contents of P. brevitarsis larvae were higher than those of other edible insects such as Tenebrio molitor and Allomyrina dichotoma [ 18 , 19 ]. Human studies have reported a significantly reduced risk of cognitive decline and dementia in a population sample with high consumption of dietary unsaturated fatty acids such as PUFA and MUFA [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, in the results of the analysis of the composition of fatty acids in FPB, palmitic acid, oleic acid, and linoleic acid were the major fatty acids detected ( Table 1 ). Consistent with our study, previous studies have reported that the essential amino acid and unsaturated fatty acid contents of P. brevitarsis larvae were higher than those of other edible insects such as Tenebrio molitor and Allomyrina dichotoma [ 18 , 19 ]. Human studies have reported a significantly reduced risk of cognitive decline and dementia in a population sample with high consumption of dietary unsaturated fatty acids such as PUFA and MUFA [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, few studies using P. brevitarsis larvae fermented with Bacillus subtilis ( B. subtilis ) have been reported. In our previous study, P. brevitarsis larvae were fermented with the beneficial microorganism B. subtilis to increase their utility as food and to increase the amino acid content [ 18 ]. The results confirmed that the content of free amino acids, including essential amino acids, increased compared to another previously reported study [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serum alcohol and acetaldehyde concentrations were measured using commercial kits (Megazyme Int., Bray, Ireland). AUC was measured using the trapezoidal method (for the time interval of the obtained blood samples) [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…The control and NS groups were provided drinking water the same way. After eight weeks of treatment with sample and alcohol, experimental animals were sacrificed for serum analysis and evaluation of fatty liver-related biomarkers, and blood was collected from the abdominal vena cava and liver was obtained [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation